Efek flavonoid daun srikaya (Annona squamosa (L)) terhadap pemacuan ekspresi P53 sel HeLa - Laela Hayu Nurani; Suwidjiyo Pramono; Sudjadi . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Flavonoids are secondary metabolites with many activities such as an anticancer and an antioxidant. Annona squamosa L. leave are reported contain flavonoids. Annona squamosa flavonoids were isolated from ether fraction and separated by paper chromatography with acetic acid 15% as mobile phase. Four flavonoids with Rf value of 0.11, 0.23, 0.46 and 0.78 were detected as 5-hydroxy-7-R-flavonol (1), 5,3’,4’-trihydroxy-7-R-flavonol (2), 5-hydroxy-7-Rflavanone (3) and 7-R-flavanone (4), respectively. The cytotoxicity of each flavonoid on Hella cell line was carried out using direct counting method and the p53 expression was done with immunocytochemistry. The result showed that LC50 of flavonoid 1, 2, 3 and 4 was 12.63±3.4, 18.47±3.4, 75.74±6.2 and 204.4±14.0 µg/mL. Twelve µg/mL of 5-hydroxy-7-R-flavonol (1) increased p53 expression of eleven fold than control.Keywords: Annona squamosa, HeLa, flavonoid, p53